CULTURAL SENSITIVITY IN TRANSLATION - Makhliyo Azimova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Being culturally sensitive is vitally important as the aspect of translation in order to accurately and clearly convey the meaning of the given text while not showing and rudeness to the cultural context of both source and target language. In this article I will try to explain the fundamental role of cultural sensitivity during the process of translation by assessing its own importance, problems, strategies and examples. So as to translate appropriately, possessing the deep understanding of cultural nuances which resonates different audience and navigating idiomatic language with expressions is the most important part of translation. If a translator culturally and traditionally literate, he/she can bridge linguistic and cultural divides to improve greater understanding and appreciation between cultural boundaries.